An assessment of the techno-economic, geopolitical and strategic feasibility of exporting hydrogen from Iceland to Europe - Kit Edward Robert Pickford 1993- (2021)
The utilisation of renewable hydrogen in the global energy system is seeing a resurgence of interest, as part of the drive to reduce carbon emissions and to mitigate the worst effects of anthropogenic climate change. The large volumes required to meet forecasted demand raise questions over the viability of international trade in hydrogen and how this will impact the geopolitical landscape. In the context of Europe’s hydrogen strategy, this thesis focuses on the case of exporting hydrogen from Iceland to Europe. Specifically, its techno-economic viability, socio-economic desirability for Iceland, strategies for implementation and geopolitical implications. Several recent studies focus on the international trade in hydrogen, but none provide a comprehensive assessment of trade between Iceland and Europe. Literature on the geopolitical implications of hydrogen trade was found to be lacking, particularly compared to that on conventional energy sources. An adapted cost model was used to assess the techno-economic viability of hydrogen export between Iceland and Europe and an extensive literature review to assess strategy and geopolitical implications. Four hydrogen pathways were assessed between 2022-2050. Though no pathway reached economic viability, it was found that transporting hydrogen as ammonia presented the most feasible opportunity. Cost reductions greater than those assumed in the literature are plausible; Iceland should therefore focus initially on building a domestic hydrogen market, whilst tentatively exploring avenues for export. The European hydrogen strategy presents positive market opportunities for Iceland and has negligible negative geopolitical implications. For Europe, however, pursuing the creation of a hydrogen market presents great geopolitical uncertainty and should be a focus for further research. Vinsældir endurnýjanlegs vetnis í orkukerfum hafa aukist vegna jákvæðra áhrifa sem það hefur á minnkun á kolefnisútblæstri og framlagi til minnkunar loftlagsbreytingar. Spár um magns vetnis sem ...